ALTERATION OF COLONY MORPHOLOGY OF MYCOBACTERIA ASSOCIATED WITH LYSOGENY - White, Arthur (1962)
White, Arthur (University of Louisville, Louisville, Ky.), Frances Foster, and Linda Lyon. Alteration of colony morphology of mycobacteria associated with lysogeny. J. Bacteriol. 84:815–818. 1962.—Smooth colonies of mycobacteria were obtained from previously rough strains after exposure to phages R(1) and D-32 in a higher frequency than could be expected from selection of mutants alone. A high proportion of the smooth colonies were lysogenized. Smooth lysogenized strains maintained both lysogeny and smooth morphology after repeated subcultures on agar or in Tween media. The available evidence suggests that lysogeny with certain mycobacteriophages alters colony morphology by a means other than selection of mutants.